Dorsoventral patterning in the Drosophila retina by wingless. - Heberlein, U.; Borod, E.R.; Chanut, F.A. (Development, 1998)
The eye imaginal disc displays dorsal-ventral (D-V) and anterior-posterior polarity prior to the onset of differentiation, which initiates at the intersection of the D-V midline with the posterior margin. As the wave of differentiation progresses anteriorly, additional asymmetry develops as ommatidial clusters rotate coordinately in opposite directions in the dorsal and ventral halves of the disc; this forms a line of mirror-image symmetry, the equator, which coincides with the D-V midline of the disc. How D-V pattern is established and how it relates to ommatidial rotation are unknown. Here we address this question by assaying the expression of various asymmetric markers under conditions that lead to ectopic differentiation, such as removal of patched or wingless function. We find that D-V patterning develops gradually and that wingless plays an important role in setting up this pattern. We show that wingless is necessary and sufficient to induce dorsal expression of the gene mirror prior to the start of differentiation and also to restrict the expression of the WR122 marker to differentiating photoreceptors near the equator. In addition, we find that manipulations in wingless expression shift the D-V axis of the disc as evidenced by changes in the expression domains of asymmetric markers, the position of the site of initiation and the equator, and the pattern of epithelial growth. Thus, Wg appears to coordinately regulate multiple events related to D-V patterning in the developing retina.